The feelings book - Parr, Todd. (New York : Little, Brown, 2009)
Children express different moods, including "I feel very mad," "I feel like reading books all day," and "I feel like wearing funny underwear.".
"Megan Tingley books."
School Library Journal
1.6
K-3.
K-3
Keywords: Emotions -- Juvenile fiction; Emotions -- Fiction; Emotions -- Fiction